General physical fitness building methodology for beginner judokas - Maltsev, G. S.; Ryabov, A. A.; Ryabova, E. K.; Fomenkovaz, Y. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to develop and test benefits of a new body conditioning model for beginner judo groups.